Key roles of autophagosome/endosome maturation mediated by Syntaxin17 in methamphetamine-induced neuronal damage in mice - Xi Wang; Miaoyang Hu; Jingrong Chen; Xinyu Lou; Hongchao Zhang; Muhan Li; Jie Cheng; Tengfei Ma; Jianping Xiong; Rong Gao; Xufeng Chen; Jun Wang (BMC, 2024)
Abstract Background Autophagic defects are involved in Methamphetamine (Meth)-induced neurotoxicity. Syntaxin 17 (Stx17), a member of the SNARE protein family, participating in several stages of autophagy, including autophagosome-late endosome/lysosome fusion. However, the role of Stx17 and potential mechanisms in autophagic defects induced by Meth remain poorly understood. Methods To address the mechanism of Meth-induced cognitive impairment, the adenovirus (AV) and adeno-associated virus (AAV) were injected into the hippocampus for stereotaxis to overexpress Stx17 in vivo to examine the cognitive ability via morris water maze and novel object recognition. In molecular level, the synaptic injury and autophagic defects were evaluated. To address the Meth induced neuronal damage, the epidermal growth factor receptor (EGFR) degradation assay was performed to evaluate the degradability of the "cargos" mediated by Meth, and mechanistically, the maturation of the vesicles, including autophagosomes and endosomes, were validated by the Co-IP and the GTP-agarose affinity isolation assays. Results Overexpression of Stx17 in the hippocampus markedly rescued the Meth-induced cognitive impairment and synaptic loss. For endosomes, Meth exposure upregulated Rab5 expression and its guanine-nucleotide exchange factor (GEF) (immature endosome), with a commensurate decreased active form of Rab7 (Rab7-GTP) and impeded the binding of Rab7 to CCZ1 (mature endosome); for autophagosomes, Meth treatment elicited a dramatic reduction in the overlap between Stx17 and autophagosomes but increased the colocalization of ATG5 and autophagosomes (immature autophagosomes). After Stx17 overexpression, the Rab7-GTP levels in purified late endosomes were substantially increased in parallel with the elevated mature autophagosomes, facilitating cargo (Aβ42, p-tau, and EGFR) degradation in the vesicles, which finally ameliorated Meth-induced synaptic loss and memory deficits in mice. Conclusion Stx17 decrease mediated by Meth contributes to vesicle fusion defects which may ascribe to the immature autophagosomes and endosomes, leading to autophagic dysfunction and finalizes neuronal damage and cognitive impairments. Therefore, targeting Stx17 may be a novel therapeutic strategy for Meth-induced neuronal injury.